2000
DOI: 10.1111/j.1532-5415.2000.tb05000.x
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Care for Patients Aged 55 Years and Older: Report from a Practice‐Based Research Program

Abstract: Further investigation of the PDI and a decrease in pain medication use as outcome measures seems warranted. The descriptive information in this study may assist providers of care to older adults to better understand their patients' use of chiropractic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…[16][17][18] Open-ended responses for all 3 samples were coded by a research assistant who checked off returned surveys prior to key entry, separating the identifier code from the survey to preserve anonymity of the responses. All data were key double-entry verified and managed in a relational database according to set protocols.…”
Section: Data Collection Management and Analysismentioning
confidence: 99%
“…[16][17][18] Open-ended responses for all 3 samples were coded by a research assistant who checked off returned surveys prior to key entry, separating the identifier code from the survey to preserve anonymity of the responses. All data were key double-entry verified and managed in a relational database according to set protocols.…”
Section: Data Collection Management and Analysismentioning
confidence: 99%
“…[7][8][9] Even where US community-based data have been used 10 the analysis is based on data that are now dated. More recently studies have been done through an established chiropractic practice network, 11,12 but these are convenience samples and are therefore more constrained in terms of generalizations. The only recent data that can be generalized are from 2 previous publication from this project 13,14 which are based on randomly selected practices and patients in cluster samples in North America.…”
mentioning
confidence: 99%
“…56,57 A recent practice based study suggested some evidence for the efficacy of chiropractic management for older adults. 58 There is a need however for more research specifically targeted at older adults, not just for chiropractic but for all treatments of back pain. The chiropractic profession has a great opportunity to be the leader in research for this important public health problem.…”
Section: Chiropractic Geriatrics and Public Healthmentioning
confidence: 99%